The appraisal of the situation of the palliative care in Poland in 2017 - Ciałkowska-Rysz, Aleksandra; Dzierżanowski, Tomasz (Medycyna Paliatywna/Palliative Medicine, 2018)
The assessment of the situation, financing and accessibility of palliative care in Poland in 2017 have been done in this paper. We used data from the National Health Fund, the Ministry of Health, the Centre of Education for Nurses and Midwives, the Centre of Medical Examinations, and consultants’ reports. We demonstrated that the access to palliative and hospice care services warranted by the insurance system in Poland is regionally diversified. Disproportions between voivodeships concern the number of entities, expenditures per capita, and the accessibility to services. Home care is the best accessible. The implementation of new pricing of palliative and hospice care services in 2017 resulted in over 30% increase in expenditures on palliative care. The highest growth referred to in-patient care. The human staff in palliative care may be appraised as satisfactory. However, along with the increase of demand for palliative care, the demand for specialistic staff will be growing too.